Case Report: Van Wyk–Grumbach syndrome presenting as vaginal bleeding: diagnostic value of pituitary and pelvic imaging - Cao, Yuqing; Zhao, Xiaorui; Huang, Wenjing; Xi, Yue; Wu, Huiying (Frontiers in Pediatrics, 2026)
BackgroundVan Wyk–Grumbach syndrome (VWGS) is a rare endocrine disorder caused by long-standing severe primary hypothyroidism, characterized by pseudoprecocious puberty and polycystic ovarian lesions. Owing to its overlapping features with central precocious puberty and ovarian tumors, misdiagnosis is common and may lead to unnecessary surgical intervention or delayed treatment.Case presentationWe report the case of an 8-year-old girl who presented with vaginal bleeding. Physical examination revealed partial precocious puberty (Tanner stage 3). Laboratory evaluation demonstrated markedly elevated thyroid-stimulating hormone (TSH >150 mIU/mL) and decreased thyroid hormones, consistent with primary hypothyroidism. Imaging revealed symmetrical pituitary hyperplasia (vertical diameter ≈17.7 mm) and large bilateral multilocular ovarian cysts.ConclusionThis case emphasizes the necessity of routine thyroid function screening in the differential diagnosis of pediatric precocious puberty WITH POOR LINEAR GROWTH and ovarian cysts. The coexistence of pituitary hyperplasia, bilateral ovarian cysts, and severe biochemical hypothyroidism represents the diagnostic triad of VWGS. Prompt levothyroxine replacement therapy rapidly reversed clinical manifestations and imaging abnormalities, preventing unnecessary surgery. These findings provide key diagnostic insights for pediatric endocrinologists and radiologists.